Designing a Simple Microscope as an Alternative Learning Media with SolidWorks Software - Adiyatma, Jovan; Armanda, Rizal Endrya; Setiaji, Bayu (Faculty of Science and Education, UIN Walisongo Semarang, 2024)
Microscopes are essential as media or teaching aids for prospective educators to achieve learning goals. However, there are still obstacles in their application in the form of quite expensive costs. Often, educational aids have a sizeable nominal value for a school. Teaching aids are costly and prone to damage or loss if students use them frequently, and it is difficult and expensive to find replacements if they are damaged, so teachers are afraid to use them. To overcome this problem, this study provides another alternative design, namely the design of teaching aids that are still useful and function well for learning through the design of microscope teaching aids. The research method used is a model research design using Solidworks software. The development of learning tools compiled in this study refers to the type of 4-D development (Four-D model), which consists of 4 stages: the define stage, the design stage, the development stage, and the dissemination. The research carried out three stages, namely the definition stage (Define), the design stage (Design), and the development stage (Develop). In the results of the design draft, questions were asked of the informants; it was concluded that a proper microscope was a microscope that worked according to its specifications, namely being able to see tiny or micro-objects. The clarity of the lens and the maximum magnification are also factors in the feasibility of the microscope. This research can be concluded as a simple microscope design using the Solidworks application, which is suitable for use as an alternative learning media. If the design of this tool is to be made, then the selection of materials and mechanisms needs further research and trials.